A Disilene Base Adduct with a Dative Si–Si Single Bond. Issue 5 (22nd December 2015) - Schweizer, Julia I.; Scheibel, Markus G.; Diefenbach, Martin; Neumeyer, Felix; Würtele, Christian; Kulminskaya, Natalia; Linser, Rasmus; Auner, Norbert; Schneider, Sven; Holthausen, Max C.
Abstract: An experimental and theoretical study of the base‐stabilized disilene1 is reported, which forms at low temperatures in the disproportionation reaction of Si2 Cl6 or neo ‐Si5 Cl12 with equimolar amounts of NMe2 Et. Single‐crystal X‐ray diffraction and quantum‐chemical bonding analysis disclose an unprecedented structure in silicon chemistry featuring a dative Si→Si single bond between two silylene moieties, Me2 EtN→SiCl2 →Si(SiCl3 )2 . The central ambiphilic SiCl2 group is linked by dative bonds to the amine donor and the bis(trichlorosilyl)silylene acceptor, which leads to push–pull stabilization. Based on experimental and theoretical examinations a formation mechanism is presented that involves an autocatalytic reaction of the intermediately formed anion Si(SiCl3 )3 − with neo ‐Si5 Cl12 to yield1 . Abstract : Give and take : A perchlorodisilene amine adduct with an unusually bent structure (see picture) was isolated by freeze‐quench crystallization. The quantum‐chemical bond analysis discloses dative N1→Si1 and Si1→Si2 bonds leading to a push–pull stabilization of the central SiCl2 group.